Figuras penales en tensión con un ordenamiento neutral a la discapacidad en Chile - Purán Rosas, Violeta Catalina (2025)
The publication of the Convention on the Rights of Persons with Disabilities generated fundamental changes in international legal frameworks by adopting a social model of disability, thereby moving away from the traditional medical approach. This new paradigm has prompted significant transformations in civil and health law, challenging traditional legal mechanisms such as interdiction and guardianship. However, its impact on criminal law remains limited, with traditional legal concepts such as criminal incapacity, security measures and dangerousness assessments still prevailing, which are considered ableist and discriminatory according to international standards. This article critically addresses these legal figures within Chile, arguing that the current framework for attributing criminal responsibility discriminates against persons with disabilities. For that purpose, it examines the concept of “disability-neutral legal systems” proposed by Flynn and Arstein-Kerslake (2017), and explores structural difficulties in effectively implementing this approach within Chilean criminal law. Finally, it emphasizes the urgent need for doctrinal reflection to develop inclusive criminal justice systems that align with the human rights of persons with disabilities.